Analisis Penjadwalan Proyek Menggunakan Critical Path Method (CPM) Studi Kasus pada Pembangunan Gapura Taman Hutan Lindung Kota Langsa - Tasha Nadia Mulia; safrizal surbakti; Riny Candra (Jurnal Penelitian Ekonomi Akuntansi, 2023)
Scheduling is an important thing to do when completing a project. But sometimes the implementation deviates from the plan, so it is necessary to supervise and control the project so that the completion of the project is not delayed. Such was the case with the Langsa City Forest Park gate construction project where the completion of this project was pushed back a few days from scheduled. Delays occur due to hampered availability of materials needed, as well as weather and field conditions. So thatthis research was carried out with the aim of knowing the project control method in the Langsa City Forest Park gate construction project and to find out the comparison of project completion time using the CPM method with the Bar Chart method used by CV. Mechanical Structure. This study uses CPM (Critical Path Method) to determine network planning, critical activities, and critical paths, as well as analyze the optimal duration and cost needed for the Langsa City Forest Park gate construction project to avoid delays. Data collection techniques are carried out through interviews, direct observation, and documentation. In this study, it is known that the normal duration of the project is 21 weeks with a total cost of Rp 1,223,049,144.00. After using the CPM method, it is known that the critical path lies in activities A–C–E–G–H–I–J–K. The project can be completed with a duration of 11 weeks and costs Rp 1,488,737,722.90